Bond-shift isomers: the co-existence of allenic and propargylic phenylnitrile imines. Issue 79 (5th August 2015) - Nunes, Cláudio M.; Reva, Igor; Fausto, Rui; Bégué, Didier; Wentrup, Curt
Abstract : Two bond-shift isomers of phenylnitrile imine resulting from photochemistry of 5-phenyltetrazole. Abstract : We discovered a 1, 3-dipolar species co-existing in two different structures. Photolysis of matrix-isolated 5-phenyltetrazole generates two forms of phenylnitrile imine: propargylic and allenic. They are not resonance structures but correspond to different energy minima, representing bond-shift isomers. These distinct species were characterized spectroscopically and confirmed by calculations up to the CASSCF(14, 12) theory level.